(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Vocabulary acquisition remains a persistent challenge for EFL learners across different educational systems, making effective learning strategies essential for academic success. This study examines Vocabulary Learning Strategies (VLS) used by undergraduate English students in Indonesia and Pakistan focusing on differences influenced by educational and cultural contexts. Using a descriptive quantitative method, data was collected through a closed-ended questionnaire from 114 students across seven universities. The questionnaire, adapted from Goundar (2019) and based on Gu and Johnson’s (1996) framework, categorized VLS into meta cognitive, cognitive, memory, and activation strategies. Data analysis using SPSS included descriptive statistics, normality tests, t-tests, Mann-Whitney U tests, and Kruskal-Wallis analysis. The results revealed significant differences in VLS preferences, with cognitive strategies being the most dominant in both groups. However, Pakistani students demonstrated higher meta cognitive strategy use than their Indonesian counterparts. These findings highlight the impact of educational systems on VLS selection. The study suggests incorporating meta cognitive and activation strategies into language learning curricula to enhance students’ vocabulary acquisition.